Modulation of amyloid β-protein clearance and Alzheimer’s disease susceptibility by the LDL receptor–related protein pathway - Kang, David E. (American Society for Clinical Investigation, 2000)
Susceptibility to Alzheimer’s disease (AD) is governed by multiple genetic factors. Remarkably, the LDL receptor–related protein (LRP) and its ligands, apoE and α2M, are all genetically associated with AD. In this study, we provide evidence for the involvement of the LRP pathway in amyloid deposition through sequestration and removal of soluble amyloid β-protein (Aβ). We demonstrate in vitro that LRP mediates the clearance of both Aβ40 and Aβ42 through a bona fide receptor-mediated uptake mechanism. In vivo, reduced LRP expression is associated with LRP genotypes and is correlated with enhanced soluble Aβ levels and amyloid deposition. Although LRP has been proposed to be a clearance pathway for Aβ, this work provides the first in vivo evidence that the LRP pathway may modulate Aβ deposition and AD susceptibility by regulating the removal of soluble Aβ.